Protective effects of carbonic anhydrase inhibition in brain ischaemia in vitro and in vivo models. (1st January 2021) - Dettori, Ilaria; Fusco, Irene; Bulli, Irene; Gaviano, Lisa; Coppi, Elisabetta; Cherchi, Federica; Venturini, Martina; Di Cesare Mannelli, Lorenzo; Ghelardini, Carla; Nocentini, Alessio; Supuran, Claudiu T.; Pugliese, Anna Maria; et al.
Abstract: Ischaemic stroke is a leading cause of death and disability. One of the major pathogenic mechanisms after ischaemia includes the switch to the glycolytic pathway, leading to tissue acidification. Carbonic anhydrase (CA) contributes to pH regulation. A new generation of CA inhibitors, AN11-740 and AN6-277 and the reference compound acetazolamide (ACTZ) were investigated in two models of brain ischaemia: in rat hippocampal acute slices exposed to severe oxygen, glucose deprivation (OGD) and in an in vivo model of focal cerebral ischaemia induced by permanent occlusion of the middle cerebral artery (pMCAo) in the rat. In vitro, the application of selective CAIs significantly delayed the appearance of anoxic depolarisation induced by OGD. In vivo, sub-chronic systemic treatment with AN11-740 and ACTZ significantly reduced the neurological deficit and decreased the infarct volume after pMCAo. CAIs counteracted neuronal loss, reduced microglia activation and partially counteracted astrocytes degeneration inducing protection from functional and tissue damage.